Study of Management of Hydrocephalus Secondary to Infective Meningitis by Ommaya Reservoir and its Conversion Rate in Ventriculoperitoneal Shunt - Jain, Jayant; Bansod, Himanshu; Mahor, Devendra; Gupta, Vijay Kumar; Attry , Sanjeev (Nepal Journal of Neuroscience, 2024)
Introduction The study aimed to establish the role of Ommaya reservoir in the management of hydrocephalus secondary to infective meningitis and to study the conversion rate of Ommaya reservoir into ventriculoperitoneal shunt. Material & methods: A Non-Randomized, prospective, single institute study, conducted over 50 patients fulfilling inclusion criteria done in the Neurosurgery Department of a tertiary health center between January 2023 and June 2024, for one and a half years. Results: Majority of the patients with hydrocephalus secondary to infective meningitis were males (78%) compared to females (22%). Majority of the patients in this study who had hydrocephalus secondary to infective meningitis were adults of age more than 14 years (62%) and remaining (38%) were of pediatric age group. Out of 50 patients, majority of patients (60%) presented in altered sensorium. Majority of the patients were diagnosed with Tubercular Meningitis (84%) followed by Pyogenic Meningitis (16%). Conclusion: Ommaya reservoir placement and daily aspiration from the reservoir leads to a reduction in CSF total protein and cell count back to normal range. This provides us with an alternative surgical approach to avoid VP shunt surgeries and their associated complications.